1985
DOI: 10.1056/nejm198502143120703
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Clinical Trial of Peritoneal Lavage for the Treatment of Severe Acute Pancreatitis

Abstract: We performed a multicenter, randomized, controlled clinical trial of therapeutic peritoneal lavage (2 liters per hour for three days) in 91 patients with severe acute pancreatitis. Patients were entered into the study if severe pancreatitis was indicated by multiple laboratory criteria or diagnostic peritoneal lavage. All patients received full supportive treatment. The median time between the onset of symptoms and randomization was 38 hours. Forty-six patients were assigned to the control group and 45 to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
2
3

Year Published

1986
1986
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(64 citation statements)
references
References 20 publications
0
58
2
3
Order By: Relevance
“…Infected pancreatic necrosis develops in approximately 20% of patients with severe acute pancreatitis, with a mortality rate of approximately 30% (19). A few randomized controlled trials have reported that peritoneal lavage does not reduce the incidence of complications; however, in these reports, the duration of peritoneal lavage was only four days or less (13,15). In contrast, in the present study, the median duration of peritoneal lavage was seven days, and the incidence of infected pancreatic necrosis was 4%.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Infected pancreatic necrosis develops in approximately 20% of patients with severe acute pancreatitis, with a mortality rate of approximately 30% (19). A few randomized controlled trials have reported that peritoneal lavage does not reduce the incidence of complications; however, in these reports, the duration of peritoneal lavage was only four days or less (13,15). In contrast, in the present study, the median duration of peritoneal lavage was seven days, and the incidence of infected pancreatic necrosis was 4%.…”
Section: Discussioncontrasting
confidence: 53%
“…Peritoneal lavage was started within 72 hours from the initial onset of symptoms in 20 patients (87%). The duration of peritoneal lavage was seven (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) days. The duration of peritoneal lavage was correlated with the SIRS score (r=0.52; p=0.036), number of prognostic factors according to the revised Japanese criteria (r=0.70; p= 0.0054), Ranson score (r=0.49; p=0.049) and serum Creactive protein level (r=0.65; p=0.0096) at the start of peritoneal lavage.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However a multicenter, prospective, randomised, controlled trial of patients who received standard supportive therapy with or without hourly two litre peritoneal dialysis exchanges for three days found no difference in mortality or complication rates (26). Thus, the supposed beneficial effects of peritoneal dialysis in acute pancreatitis (27) are a matter of controversy and the beneficial effect of the addition to the peritoneal dialysis solution of antibiotics or antiproteinases remains speculative.…”
Section: Acute Pancreatitismentioning
confidence: 99%
“…Eight randomized prospective clinical trials evaluating the influence of continuous peritoneal lavage in patients with acute pancreatitis were performed, but led to divergent results [38,39,40,41,42,43,44,45]. A meta-analysis, however, showed that this therapeutic procedure was not associated with any improvement in mortality or morbidity [46].…”
Section: Principle Of Minimizing Toxicitymentioning
confidence: 99%